FAKTOR-FAKTOR YANG MEMENGARUHI KEMISKINAN RUMAH TANGGA TANI DI DESA MATANTIMALI KECAMATAN MARAWOLA BARAT KABUPATEN SIGI - Astuti, Ade Irma; Antara, Made; Rauf, Rustam Abd (AGROTEKBIS, 2018)
Matantimali village is a part of Sigi regency that currently has 147 households category zedas pre-prospero us families and the majority of them work in farming sector. This research was conducted in Matantimali village located exactly in West Marawola sub district of Sigi regency.The aim of this research was to determine whether such variables as education, number of family dependents, and asset ownership affected the poverty of the farmer households. This research was conducted fromJuly to August 2016.The samplesselected 50 households. Method used in this research was multiple linear regression analysis. The dependent (X1) and land area variables individually had significant effect on the income of the farmer households in Matantimali village.  Education dummy (DP) of those who weregraduated would increase the income compared with those who were not.